A NOVEL TOURISM COMPETITIVENESS RANK - Zaher, Hegazy; Hafez, Ahmed (International Journal of Research -GRANTHAALAYAH, 2017)
This paper proposes a novel tourism rank to arrange countries in tourism. The proposed rank is based on fifteen factors, the fourteen factors affecting the tourism rank considered in the Travel & Tourism competitiveness reports and the number of tourist arrivals considered in United Nations World Tourism Organization rank. The proposed method gives significant differences compared to the traditional ranks used by the Travel & Tourism competitiveness reports and United Nations World Tourism Organization rank.